2021
DOI: 10.1182/bloodadvances.2020002832
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia favors chemoresistance in T-ALL through an HIF1α-mediated mTORC1 inhibition loop

Abstract: Resistance to chemotherapy, a major therapeutic challenge in the treatment of T-cell acute lymphoblastic leukemia (T-ALL), can be driven by interactions between leukemic cells and the microenvironment that promote survival of leukemic cells. The bone marrow, an important leukemia niche, has low oxygen partial pressures that highly participate in the regulation of normal hematopoiesis. Here we show that hypoxia inhibits T-ALL cell growth by slowing down cell cycle progression, decreasing mitochondria activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Cancer triggers metabolism, angiogenesis, and erythropoiesis to counteract the disadvantages of hypoxia, of which HIF-1 is the central regulatory mechanism of hypoxia that acts by upregulating its downstream genes (216,217). HIF-1 is the main transcription factor that induces the expression of almost all genes encoding glucose transporters and glycolytic key enzymes (218,219), which allows hypoxic cancer cells to absorb glucose more efficiently, metabolize pyruvate to lactate, activate multi-drug resistance gene, and induce chemoresistance (220,221). Hypoxia has synergistic effects with acidosis on inducing chemoresistance by upregulating the expression of fatty acid synthase and regulating lipid metabolism (209); it can induce acidosis by selecting glycolytic cells, and acidosis can further select cells with upregulated glycolysis and acidic resistance, thereby choosing cells with survival advantages (222).…”
Section: Microenvironment Induced Chemoresistance In Cancermentioning
confidence: 99%
“…Cancer triggers metabolism, angiogenesis, and erythropoiesis to counteract the disadvantages of hypoxia, of which HIF-1 is the central regulatory mechanism of hypoxia that acts by upregulating its downstream genes (216,217). HIF-1 is the main transcription factor that induces the expression of almost all genes encoding glucose transporters and glycolytic key enzymes (218,219), which allows hypoxic cancer cells to absorb glucose more efficiently, metabolize pyruvate to lactate, activate multi-drug resistance gene, and induce chemoresistance (220,221). Hypoxia has synergistic effects with acidosis on inducing chemoresistance by upregulating the expression of fatty acid synthase and regulating lipid metabolism (209); it can induce acidosis by selecting glycolytic cells, and acidosis can further select cells with upregulated glycolysis and acidic resistance, thereby choosing cells with survival advantages (222).…”
Section: Microenvironment Induced Chemoresistance In Cancermentioning
confidence: 99%
“…Initially, most researchers reported that mTOR signaling activation may contribute to chemoresistance and ALL progression [ 17 , 23 , 54 ]. On the contrary, a recent paper showed that activation of mTORC1 pathway may help suppress the drug resistance of T-ALL in hypoxic niches [ 55 ]. It is intriguing that while AMPK functions as an antagonist of mTOR [ 56 ]; both AMPK and mTOR signaling pathways were inhibited in NALM-6/HDR cells, which is consistent with the findings in CEM-C7/HDR [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…T-ALL switch their metabolic programs in a similar way to normal HSCs when cultured in low oxygen [200]. Reduced mitochondrial activity and cell cycle progression in these low oxygen niches increases glycolysis and lowers their sensitivity to vincristine and cytarabine (cell cycle-related drugs) and dexamethasone, compared with T-ALL cells grown under normoxic conditions [201]. While low oxygen levels suppressed the activity of mTORC1, it increased the activity of HIF1α with the concomitant increase in the expression of HIF1α effector genes such as, VEGF, GLUT3 and CXCR4 to reduce mitochondrial activity and as such ROS levels in ALL [201].…”
Section: Redox Homeostasis In Allmentioning
confidence: 99%